Basic Perceptions of Socialism and its Political Spell Out; Persuasion of the Intellectuals - Mr. Zia Ur Rehman (jihat-ul-islam, 2023)
Socialism is basically defined as a political and economic theory of social organizations which in its acolyte’s sense is the ambassador of human rights. This perception advocates that the means of production, distribution, and exchange should be regulated and governed by the community. This research paper aims to elucidate what are the basic schools of thought on communism and Bolshevism. This paper also highlights the political aspects of this socialist ideology. It will also be highlighted in this paper what is the basic wrangle and discrepancy between socialism and communism. Concluding the topic it will be chewed over that what are the various spell out of different intellectuals regarding the implementation of the hierarchy of socialism. What pros and cons this system has in it will also be discussed in the paper. Chicago Manual 2017 is used for the writing of the paper.